Bit and Power Allocation in Constrained Multicarrier Systems: The Single-User Case. (15th July 2007) - Papandreou Papandreou, Nikolaos Nikolaos; Antonakopoulos Antonakopoulos, Theodore Theodore
Abstract : Multicarrier modulation is a powerful transmission technique that provides improved performance in various communication fields. A fundamental topic of multicarrier communication systems is the bit and power loading, which is addressed in this article as a constrained multivariable nonlinear optimization problem. In particular, we present the main classes of loading problems, namely, rate maximization and margin maximization, and we discuss their optimal solutions for the single-user case. Initially, the classical water-filling solution subject to a total power constraint is presented using the Lagrange multipliers optimization approach. Next, the peak-power constraint is included and the concept of cup-limited waterfilling is introduced. The loading problem is also addressed subject to the integer-bit restriction and the optimal discrete solution is examined using combinatorial optimization methods. Furthermore, we investigate the duality conditions of the rate maximization and margin maximization problems and we highlight various ideas for low-complexity loading algorithms. This article surveys and reviews existing results on resource allocation in constrained multicarrier systems and presents new trends in this area.